2008
DOI: 10.1109/lmwc.2007.915037
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Measurements on a High-Reliability RF-MEMS Contact Switch

Abstract: Radio frequency microelectromechanical systems (RF MEMS) cantilever contact switches have been tested for lifetime. The mean cycles-to-failure measured on an ensemble of switches was 430 billion switch cycles. The longest lifetime exhibited without degradation of the switch was 914 billion switch cycles. The devices were switched at 20 kHz with an incident RF frequency of 10 GHz and an incident RF power of 20 dBm. Testing was performed continuously over a period of approximately 18 months. The switches were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…The human body can build up an electric potential more than 1000 volts, which can prove to be fatal for MEMS devices [58]. Numerous test standards, experimental procedures, and processes have been demonstrated to overcome the open, short circuit and ESD problems [59,60]. However, this area still requires more attention from researchers and academicians in order to rectify the reliability issues in these sophisticated MEMS devices.…”
Section: Reliabilitymentioning
confidence: 99%
“…The human body can build up an electric potential more than 1000 volts, which can prove to be fatal for MEMS devices [58]. Numerous test standards, experimental procedures, and processes have been demonstrated to overcome the open, short circuit and ESD problems [59,60]. However, this area still requires more attention from researchers and academicians in order to rectify the reliability issues in these sophisticated MEMS devices.…”
Section: Reliabilitymentioning
confidence: 99%
“…McClure [105] proposed a mechanism for creating a charge distribution in the dielectric of the MEMS device exposed to nuclear radiation. Newman et al [106] presented the contact surface of a wafer-packaged RF MEMS switch damaged by ESD. It exhibits 914 billion switch cycles at 20 kHz with an incident RF frequency of 10 GHz without degradation, which has the longest lifetime of operation ever reported.…”
Section: B Dielectric Breakdown Due To Electrostatic Dischargementioning
confidence: 99%
“…To date, several test setups have been reported that have worked around some of these challenges to obtain useful device characteristics. In [2], the authors presented a RF-MEMS contact switch test setup that operated at a 20 kHz cycling rate. An RF input to the switch and a crystal detector on the output were used to monitor the contact characteristics and this data was periodically sampled.…”
Section: Introductionmentioning
confidence: 99%